Serpentinization Study On Ultramafic Rock at Morombo Area, Lasolo Islands District, North Konawe Regency, Southeast Sulawesi, Indonesia - Hasria; Febiyanti; Masri; Ali Okto; Erzam S. Hasan; La Hamimu; Sawaludin; La Ode Muhammad Iradat Salihin; Wahab (UIR PRESS, 2022)
The research is in Morombo area, North Konawe Regency, Southeast Sulawesi. The purpose of this study was to determine the characteristics of serpentinized ultramafic rock and serpentine paragenesis. Research was conducted using field observations and laboratory analysis consisting of petrographic and geochemical analysis in the form of X-Ray Fluorosence (XRF). Petrographic analysis was carried out to identify the mineral content and textures in the rock and to determine the percentage of serpentine mineral presence. Both of these rocks are petrographically dominated by primary minerals olivine and clinopyroxine and secondary minerals namely lizardite, chrysotile, antiorite and opaque minerals. The XRF analysis was to determine the elements of Ni, Fe, Co, MgO, SiO2, CaO, Al2O3 and P in ultramafic rocks. The results of petrographic analysis show that serpentinized ultramafic rocks in the study area consist of serpentinized dunite and serpentinized peridotite. The formation of clay minerals in rocks does not occur because of the low serpentinization process in the rock. The results of XRF analysis showed that all samples in the bedrock showed Ni content above 0.2%. This is caused by the enrichment of Ni which is interpreted as a result of the serpentinization process along with the formation of lizardite in the rock. The serpentinization sub-processes in the study area comprised by hydration, serpentine recrystallization, and deserpentinization. Serpentine paragenesis is formed from the mid-oceanic ridge ocean floor, the orogenic phase to weathering. Substitution of Mg by Ni in ultramafic rocks will produce Ni-Serpentin. It is estimated that in the research area lizardite and chrysotile lizardite and chrysotile are the causes of Ni enrichment in bedrocks. The serpentinization characteristics of ultramafic rocks in the study area show a low to moderate level of serpentinization.